Antioxidant properties of different products and additives in white wine. (1st February 2015) - Comuzzo, Piergiorgio; Battistutta, Franco; Vendrame, Marco; Páez, Mariana Silvina; Luisi, Graziano; Zironi, Roberto
Highlights: Sulphur dioxide was the most active additive in reducing wine colour development. Ascorbic acid was a good O2 and radical scavenger but induced browning during storage. Lees were good O2 and radical scavengers but increased colour by releasing phenolics. Glutathione had radical scavenging ability in wine but increased colour during storage. Yeast derivative behave more similarly to SO2 protecting wine colour over 8 months. Abstract: Different winemaking products (ascorbic acid, glutathione, yeast lees and a yeast autolysate) were tested in comparison with sulphur dioxide, concerning radical scavenging activity (measured by DPPH assay), oxygen consumption capacity and ability to reduce wine colour and predisposition to browning. Trials were performed in white wines and model solution. SO2 was the most active in reducing wine colour development. Fresh lees and ascorbic acid were very effective in oxygen and free radical scavenging, but they both induced browning during wine storage, the former, by releasing phenolic compounds. Glutathione was also able to scavenge DPPH in wine, but less effective against oxygen, and it induced browning during storage. Surprisingly, the yeast derivative preparation was the treatment that behave more similarly to sulphiting; it was very active in scavenging DPPH, and, even without modifying oxygen consumption rate, it protected quite well wine colour over an 8 months storage time.